Original article Subependymal giant cell astrocytomas with atypical histological features mimicking malignant gliomas - Grajkowska, Wieslawa; Kotulska, Katarzyna; Jurkiewicz, Elżbieta; Roszkowski, Marcin; Daszkiewicz, Paweł; Jóźwiak, Sergiusz; Matyja, Ewa (Folia Neuropathologica, 2011)
Subependymal giant cell astrocytoma (SEGA) is a rare, benign brain tumour developing in patients with tuberous sclerosis complex (TSC). Typical histopathological findings of this neoplasm are solid sheets and perivascular pseudorosettes of large, gemistocytic, polygonal and occasionally ganglion-like cells within a fibrillated background, accompanied by spindle-shaped cells creating broad fascicles. Rich vascular stroma, and numerous calcifications are common. Mitoses, focal necrosis, and endothelial proliferation are rarely encountered. In this study we report 3 cases of SEGA out of 29 TSC patients, operated on in the Department of Neurosurgery, Children’s Memorial Health Institute, from 1990 to 2011 and retrospectively reviewed. These 3 cases exhibited distinct anaplastic features that might mimic malignant glioma. Histologically, the tumours were composed of pleomorphic, gemistocytic, polygonal, ganglion-like or multinucleated cells arranged in sheets or forming perivascular pseudorosettes. Numerous foci of necrosis, microvascular proliferation and high mitotic activity with atypical mitotic figures were documented. The Ki67 labelling index was about 15-20%. These tumours might be confused with high-grade gliomas and such a misleading diagnosis might result in aggressive radio- or chemotherapy. Despite the common statement that morphological features of anaplasia, i.e. pleomorphism, necrosis, microvascular proliferation and increased mitotic activity, are not of prognostic value, the tumour behaviour in our cases seems to be more aggressive and requires longer follow-up studies. We suggest recognizing such cases of subependymal giant cell astrocytoma as atypical SEGAs.